2016
DOI: 10.1080/15592294.2016.1226739
|View full text |Cite
|
Sign up to set email alerts
|

Stage 4S neuroblastoma tumors show a characteristic DNA methylation portrait

Abstract: Stage 4S neuroblastoma (NB) is a special type of NB found in infants with metastases at diagnosis and is associated with an excellent outcome due to its remarkable capacity to undergo spontaneous regression. As genomics have not been able to explain this intriguing clinical presentation, we here aimed at profiling the DNA methylome of stage 4S NB to better understand this phenomenon. To this purpose, differential methylation analyses between International Neuroblastoma Staging System (INSS) stage 4S, stage 4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 52 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…For example whole chromosomes gain or loss are similar between Stage 4 and Stage 4S (Bénard et al, 2008). Stage 4S specificities were finally identified from their molecular and epigenetic portraits (Bénard et al, 2008; Decock et al, 2016) opening new areas of research regarding the mechanisms contributing to their unique biology and propensity to regress spontaneously.…”
Section: Stage 4s Neuroblastoma: a Developmental Disorder With Physiomentioning
confidence: 99%
“…For example whole chromosomes gain or loss are similar between Stage 4 and Stage 4S (Bénard et al, 2008). Stage 4S specificities were finally identified from their molecular and epigenetic portraits (Bénard et al, 2008; Decock et al, 2016) opening new areas of research regarding the mechanisms contributing to their unique biology and propensity to regress spontaneously.…”
Section: Stage 4s Neuroblastoma: a Developmental Disorder With Physiomentioning
confidence: 99%
“…Stage MS NBL is usually a sporadic disease with distinct clinical and molecular features that are different from neuroblastoma stage IV. 6,7 The occurrence of synchronous tumour in monozygotic twins may suggest the presence of a common genetic background as a predisposition factor for NBL genesis. Furthermore, fetoplacental metastasis is considered when monozygotic monochorionic twins have similar tumour pathology, but only one with identifiable primary tumour, presenting spontaneously, or shortly after.…”
Section: Discussionmentioning
confidence: 99%
“…They observed hypermethylation in genes associated with subtelomeric regions. Moreover, the study showed hypermethylation of genes that are involved with neural crest development and differentiation in 4S subset compared to the tumors in stages 1, 2, or 4 [55]. Another critical gene involved in telomere maintenance is telomerase reverse transcriptase (TERT).…”
Section: Role Of Dna Methylation In Gene Expression In Neuroblastomamentioning
confidence: 99%